Financial Feasibility Analysis of Crystal Guava as Soft Candy The Krisjam's Bantarsari - Anggraini, Vira; Gandhy, Abel; Herdiyana, Herdiyana (Institute of Computer Science (IOCS), 2025)
This study aims to examine and analyze ways to enhance employee performance, investigate a conceptual model, and fill a research gap on transformational leadership style and work motivation through work discipline at PT Adis Dimension Footwear Balaraja-Tangerang Stockfit division. This study employs a causal approach and a descriptive quantitative method. This study used a sample of 190 respondents and focused on the PT Adis Dimension Footwear Balaraja-Tangerang Stockfit division. An interval scale of 1 to 10 was used to measure questionnaire responses. Software called SmartPLS Version 4.0 was used to evaluate the data. The study's findings indicate that: 1. According to the study's findings, transformational leadership significantly impacts employee performance. 2) Employee performance is significantly impacted by job motivation. 3. Work discipline is significantly impacted by transformational leadership. 4. Job discipline is significantly impacted by job motivation. 5. Employee performance is significantly impacted by work discipline. 6. The Impact of a transformative leadership style on staff performance is mediated by work discipline. 7. The relationship between work motivation and employee performance is mediated by work discipline.